PENGARUH INTENSITAS CAHAYA BUATAN TERHADAP PRODUKSI SAYURAN HIDROPONIK DI MUSIM HUJAN - Maryono, Tri (AGRONIMAL: Jurnal Ilmiah Pertanian dan Peternakan, 2025)
This study aims to analyze the effect of artificial light intensity on hydroponic vegetable production during the rainy season. Limited sunlight during the rainy season often reduces plant growth and productivity. An experimental method using a randomized block design with four light intensity treatments was applied. Observed parameters included plant height, leaf number, fresh weight, and harvest yield. Data were analyzed using variance analysis. Results indicated that artificial light significantly improved plant growth and production. Moderate to high light intensity treatments showed optimal results by supporting photosynthesis efficiency. The findings suggest that artificial lighting can serve as an effective strategy to stabilize hydroponic vegetable production during low natural light conditions. In conclusion, appropriate artificial light management enhances hydroponic productivity during the rainy season.